Effects of Lotrafilcon A and Senofilcon A Bandage Contact Lenses on Visual Outcome and Ocular Comfort After Photorefractive Keratectomy - Konuralp Yakar; Göksu Alaçamlı (Türk Oftalmoloji Dergisi)
Objectives: To compare the efficacy of two different silicone hydrogel bandage contact lenses (BCLs) in terms of visual rehabilitation and ocular discomfort following photorefractive keratectomy (PRK). Materials and Methods: This prospective study included 60 eyes of 30 patients who underwent bilateral PRK surgery to correct myopia and/or astigmatism refractive errors. Following surgery, lotrafilcon A BCLs were applied to the right eye and senofilcon A BCLs were applied to the left eye. When the BCLs were removed on postoperative day 5, subjective ocular symptoms of discomfort were evaluated on a scale of 0 to 10, where 0 indicated no discomfort and 10 indicated maximum discomfort. The postoperative spherical equivalents (SE) of both eyes were compared at 15 days and 1 month. Postoperative SE ≤ ±0.50 diopters was accepted as emmetropia. The number of patients who achieved emmetropia was also compared at 15 days and 1 month postoperatively. Results: Scores for ocular discomfort in the first 5 days postoperatively did not differ significantly between the BCLs (p>0.05). However, a statistically significant difference was observed between the two lenses in terms of SE values at postoperative 15 days and 1 month (p<0.05). Eyes fitted with the senofilcon A BCL demonstrated better postoperative visual rehabilitation. Conclusion: Although post-PRK ocular discomfort scores did not differ significantly between the two BCLs, the senofilcon A lenses performed better in terms of achieving the target SE postoperatively.